2015
DOI: 10.1097/meg.0000000000000355
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme for noninvasive assessment of liver fibrosis in autoimmune hepatitis

Abstract: Our results suggest that activated RAS may sustain hepatic fibrogenesis in AIH. Measurement of serum ACE offers an easy, accurate and inexpensive noninvasive method that differentiates significant from nonsignificant liver fibrosis in AIH. Blockade of RAS may exert beneficial effects on fibrosis progression in AIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…In addition, studies on serum ACE levels and liver fibrosis usually include a relatively small number of the patients and healthy controls. 17,18 Also, contrary to other studies, we found a higher level of serum ACE in the healthy controls (42.5 U/L) compared to the patients with CHC (36 U/L), and no correlation between serum ACE and the stages of liver fibrosis. In previous studies, the most striking results…”
Section: Figurecontrasting
confidence: 55%
See 2 more Smart Citations
“…In addition, studies on serum ACE levels and liver fibrosis usually include a relatively small number of the patients and healthy controls. 17,18 Also, contrary to other studies, we found a higher level of serum ACE in the healthy controls (42.5 U/L) compared to the patients with CHC (36 U/L), and no correlation between serum ACE and the stages of liver fibrosis. In previous studies, the most striking results…”
Section: Figurecontrasting
confidence: 55%
“…22 Measuring serum ACE levels is one of them, showing promising results in early studies, although some paradoxical outcomes have also been reported recently. [16][17][18]23 The issue of non--invasive methods has increasingly attracted many researchers, and frequently new studies on the topic are added to the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RAS was probably reported to be related to some hepatic pathogenesis, including hepatic stellate cell inflammation, proliferation, elevation of portal vein pressure, and hepatic fibrogenesis, as well [29]. RAS activation was reported in the patients with liver cirrhosis [30,31], liver inflammation [12], nonalcoholic fatty liver disease [12], and fibrosis [4,9].…”
Section: The Function Of Local Renin-angiotensin Systems In the Livermentioning
confidence: 99%
“…Moreover, blockage of RAS in the liver has improved for regeneration and inhibition of tumor progression [17]. There is an active interaction between the plasma ACE level and patient with liver fibrosis [29]. On the other hand, the local production of Ang-II might not be entirely blocked by ACE inhibitors due to that there are alternative pathways that are chymase [33].…”
Section: The Function Of Local Renin-angiotensin Systems In the Livermentioning
confidence: 99%